Cephalotheca sulfurea (Ascomycota, Sordariomycetes), a new fungal pathogen of the farmed rainbow trout Oncorhynchus mykiss - Řehulka, J; Kubátová, A; Hubka, V (Journal of fish diseases, 2016)
The first case of visceral mycotic infection due to Cephalotheca sulfurea (Cephalothecaceae, Ascomycota) is documented in farmed rainbow trout from a raceway culture system. The disease clinically manifested as a hyperaemic area in the liver of the fish, and histological examination using silver and PAS staining showed the presence of numerous foci of hyphae and spores. The causative agent was first isolated in pure culture from the liver and identified using morphological characteristics. Sequence data from ITS and LSU rDNA also clearly confirmed C. sulfurea as the causal agent. The pathogenicity of related species belonging to the family Cephalothecaceae has been well-documented in humans and dogs (superficial as well as systemic infections). However, C. sulfurea has never been reported as a pathogen of humans or animals, including marine and freshwater fishes. The morphological identification of C. sulfurea is difficult due to its similarity to several different fungal genera, and molecular methods are strongly recommended for reliable identification.
Keywords: Phialemonium; Animals; Cephalothecaceae; rainbow trout; nemoci ryb; Mycoses; DNA, Fungal; Fish Diseases; vodní hospodářství; mykózy; Aquaculture; histo-pathology; Phylogeny; Sequence Analysis, DNA; aquaculture; DNA fungální; Oncorhynchus mykiss; zvířata; sekvenční analýza DNA; fylogeneze; Sordariales